2008
DOI: 10.1002/ejic.200800269
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Based Conjugates as Polyvalent Probes for Biological Labeling

Abstract: A series of lanthanide complexes of [LnL(H2O)] composition, suitable for biological labeling has been studied, in which L is a strongly chelating ligand containing chromophoric bipyridylcarboxylate units and Ln = Sm, Eu, Gd, Tb, and Dy. For the Gd complex, a combined 17O NMR and 1H NMRD study has been performed. The water exchange rate obtained, kex298 = (5.2 ± 0.6) × 106 s–1, is slightly higher than those for [Gd(dota)(H2O)]– or [Gd(dtpa)(H2O)]2–. Transformation of the uncoordinated carboxylate function of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…0.52 ns) was longer than that in pure water (0.45 ms), indicative of a higher microviscosity. 470 The TGL image with a delay time of 100 μs clearly showed that the chelate was localized in the regions of the choroid plexus, which was a part of the blood− brain barrier mainly composed of hydrophilic epithelial cells. Lu, Jin, and co-workers upgraded a high efficient dual-color lowbackground TGL microscope to by incorporation of synchronization of a high power flash lamp with high repetition rate (1 kHz) and a robust time-gating detection unit into a commercial epi-fluorescence microscope.…”
Section: Chemical Reviewsmentioning
confidence: 98%
See 1 more Smart Citation
“…0.52 ns) was longer than that in pure water (0.45 ms), indicative of a higher microviscosity. 470 The TGL image with a delay time of 100 μs clearly showed that the chelate was localized in the regions of the choroid plexus, which was a part of the blood− brain barrier mainly composed of hydrophilic epithelial cells. Lu, Jin, and co-workers upgraded a high efficient dual-color lowbackground TGL microscope to by incorporation of synchronization of a high power flash lamp with high repetition rate (1 kHz) and a robust time-gating detection unit into a commercial epi-fluorescence microscope.…”
Section: Chemical Reviewsmentioning
confidence: 98%
“…TGL imaging is more important and advantageous in organism and tissue imaging because the increased autofluorescence and scattering compromise the contrast of the nontime-gated imaging. A Tb (III) chelate 99 (see Chart ) was used to image rat brain slices . The TGL image with a delay time of 100 μs clearly showed that the chelate was localized in the regions of the choroid plexus, which was a part of the blood–brain barrier mainly composed of hydrophilic epithelial cells.…”
Section: Long-lived Luminescent Probes For Time-resolved Photolumines...mentioning
confidence: 99%
“…The coupling is achieved either directly, e.g., in immunoassays in which the lanthanide probe is linked to a monoclonal antibody mAb, or indirectly, with the chelate being covalently bound to avidin (or biotin), and the resulting duplex being then fixed onto a biotinylated (or avidin derivatized) mAb via the strong avidin−biotin interaction (log K ≈ 10 15 ) . Alternatively, avidin may be substituted by streptavidin or bovine serum albumin (BSA) . Examples of indirect and direct coupling are depicted in Figure .…”
Section: Lanthanide Bioconjugatesmentioning
confidence: 99%
“…Multiparameter imaging is also feasible, as demonstrated by A. E. Soini et al, who used a combination of four different metal luminophores (Eu III , Tb III chelates, and Pd II , Pt II coproporphyrins) in conjunction with an organic marker (Syto 25) to image samples containing mixed populations of peripheral blood leukocytes; emission from the various luminescent stains was separated by time-resolved detection . Ligands bearing bipyridyl carboxylates units function as efficient antennae for several lanthanide ions and the Tb III bioconjugate with BSA yielded highly contrasted time-resolved luminescence images of rat brain slices …”
Section: Cell and Tissue Imagingmentioning
confidence: 99%
“…10 mm) of complex. Rough estimates of t M can be obtained in favourable cases with somewhat smaller concentrations if the 17 O experiments are very carefully performed [54] with spherical NMR samples in a 10 mm probe of a spectrometer operating at a high frequency (! 500 MHz).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%